Palaeosecular Variation of the Geomagnetic Field in the Aleutian Islands, Alaska (Dataset) ... - D. K. Bingham; D. B. Stone (Magnetics Information Consortium (MagIC), 2011)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palaeosecular Variation of the Geomagnetic Field in the Aleutian Islands, Alaska ...